2014
DOI: 10.3389/fmicb.2014.00127
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr—a still “enigmatic multitasker”

Abstract: Like other HIV-1 auxiliary proteins, Vpr is conserved within all the human (HIV-1, HIV-2) and simian (SIV) immunodeficiency viruses. However, Vpr and homologous HIV-2, and SIV Vpx are the only viral auxiliary proteins specifically incorporated into virus particles through direct interaction with the Gag precursor, indicating that this presence in the core of the mature virions is mainly required for optimal establishment of the early steps of the virus life cycle in the newly infected cell. In spite of its sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
102
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 188 publications
(250 reference statements)
0
102
0
Order By: Relevance
“…Vpr, a 14-kDa multifunctional viral protein that is efficiently packaged into virus particles, has been implicated in the regulation of apoptosis of HIV-infected cells, the efficiency and accuracy of the reverse transcription process, and the nuclear import of viral genomes (60,61). Vpr has been most intensively studied for its ability to arrest the cell cycle of HIV target cells in G 2 (62)(63)(64)(65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vpr, a 14-kDa multifunctional viral protein that is efficiently packaged into virus particles, has been implicated in the regulation of apoptosis of HIV-infected cells, the efficiency and accuracy of the reverse transcription process, and the nuclear import of viral genomes (60,61). Vpr has been most intensively studied for its ability to arrest the cell cycle of HIV target cells in G 2 (62)(63)(64)(65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…As speculated by these authors, the effect of Vpr on cytokine induction may reflect a reduction of viral genomes available for sensing that results from triggered endonuclease activity of the SLX4 complex. Following virus entry, these genomes remain packaged together with Vpr within subviral cores that uncoat and deliver viral genomes to the nucleus via poorly defined mechanisms (60,75,76). An alternative and not mutually exclusive explanation for this shaping of innate immune recognition of HIV infection is that Vpr regulates the accessibility of viral genomes to cytoplasmic DNA sensors.…”
Section: Discussionmentioning
confidence: 99%
“…10 Vpr is known to induce cell cycle arrest in G 2 /M phase. 11,12 Vpr-mediated pathogenesis in macrophages has been extensively investigated, [13][14][15] but its effects on the global molecular mechanism associated with metabolic pathways have not been characterized. Our recent SILAC-based proteomics study showed that HIV-1 Vpr overexpression in macrophages induces changes at the protein level in many of the enzymes involved in cellular metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In HIV-infected humanized mice, T regulatory lymphocytes are arrested in the G 2 phase of the cell cycle upon infection and undergo apoptosis in a vpr-dependent fashion, leading to enhanced replication (65). Besides the SLX4com, Vpr interacts with numerous cellular proteins, but the relevance of these interactions is not always clear (66). For instance, Vpr degrades UNG2, a cellular protein involved in the removal of misincorporated uracil in DNA and for which a role during the HIV-1 life cycle remains a subject of debate (67)(68)(69).…”
mentioning
confidence: 99%